Development of solid state fermentation for protease enzyme production from the Indah Water Konsortium sludge cake - Karim, Tanzeed; Alam, Md. Zahangir (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
The purpose of this research was to tackle the increase amount of sludge being produced every year from wastewater treatment plant and to figure out an alternative form of way to produce commercial protease enzyme. The wastewater sludgecake from Indah Water Konsortium Sdn Bhd was used as the substrate media and a potential low-cost media for protease enzyme production. For the design of the experiments, eleven parameters were screened and the three most significant parameters were found as glucose, tween-80 and moisture content which were further optimized using Face Centered Central Composite Design to find the optimum condition for the production. The optimization study showed that 4% glucose(w/v), 2% tween-80(v/v) and 40% moisture Content(w/v) produces the highest protease activity of 92.141 U/ml. The analysis of variance (ANOVA) also showed that the optimization model was significant with p < 0.0038 and R 2 0.8526.